Intelligent tutoring systems in e-learning environments : design, implementation, and evaluation - Stankov, Slavomir, 1947-; Glavinic, Vlado, 1952-; Rosic, Marko, 1970- (Hershey : Information Science Reference, 2011)
'This book addresses intelligent tutoring system (ITS) environments from the standpoint of information and communication technology (ICT) and the recent accomplishments within both the e-learning paradigm and e-learning systems'--Provided by publisher.
Includes bibliographical references (p. 372-406) and index.
Keywords: Intelligent tutoring systems; Web-based instruction -- Design; Education -- Effect of technological innovations on